KNOWLEDGE AWARENESS AND PRACTICE OF VARIOUS IMPLANT PROSTHETIC OPTIONS PREFERRED BY DENTAL PRACTITIONERS - Rupawat, Divya; Maiti, Subhabrata; Gopal, Tulsani Minal; Devi N, Sanjana; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
Introduction:Modern dentistry helps to restore the normal contour, function, esthetics, speech, and health regardless of the atrophy, disease, or injury of the stomatognathic system . However with traditional dentistry it becomes very difficult to achieve the above when the number of teeth remaining are less. With the advent of implant supported prosthesis and the long term success rates high quality treatment can be given to patients . Aim: To evaluate the awareness and practice of various implant prosthetic options preferred by dental practitioners in India. Material and methods: A cross-sectional survey was formulated for the dentists of India. 306 volunteers participated in this study between January to February of 2020. A validated questionnaire consisting of 16 close ended questions intended to solicit the level of participants’ knowledge concerning various options in treatment planning for implant prosthesis was circulated using online social media. Majority of questions were graded using the ‘Even scale method’. The responses were collected using web protocol forms that enabled quick and secure access to data. Results: It was found that 62.7% dentists preferred a customized abutment over a prefabricated abutment. For customized abutment 37.3% preferred a ti-base casting, 23.5% milled abutments, 23.5% 3D printed customization whereas only 15.7% preferred a conventional casting. The preferred abutment material for anterior teeth was Zirconium (62.7%) rather than cobalt chromium (4%) or titanium (33.3%). 70.5% dentists preferred to splint the prosthesis. Regarding the splinting, 47.1% preferred sexant-wise splinting, 27.5% full arch splinted whereas 25.5% quadrant wise. Conclusion: Within the limitations of the current study, it can be concluded that dentists do not regularly adhere to prosthetic principles in implant dentistry. More awareness through CDE programs, seminars etc are needed to increase knowledge among practitioners for implant prosthesis.